A Survey Paper on Password Security Techniques - Hinduja, Ankita; Sharma, Pradip (International Journal of Computer Sciences and Engineering, 2019)
This paper proposes a scheme for password management by storing password encryptions on a server. The method involves having the encryption key into a share for the user and one for the server. The user’s share shall be based only on a selected passphrase. The server’s share shall be generated from the user’s allocate and the encryption key. The security and conviction are achieved by performing both encryption and decryption on the client side. We also address the issue of countering dictionary attack by providing a further enhancement of the scheme. Password is the most ordinary method for users to authenticate themselves when entering computer systems or websites. It acts as the first line of guard against unlawful access, and it is therefore critical to maintain the usefulness of this line of guard by strictly committed a good password management policy. This paper aims to grant a set of guiding principle and best practices for handling and managing passwords.